2022
DOI: 10.3390/ijerph191710938
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Effectiveness of Policies Adopted to Enable Breastfeeding in the Philippines Are Limited by Structural and Individual Barriers

Abstract: The Philippines has adopted policies to protect, promote, and support breastfeeding on par with global standards, yet the impact of these policies is not well understood. This study assesses the adequacy and potential impact of breastfeeding policies, as well as the perceptions of stakeholders of their effectiveness and how to address implementation barriers. This mixed methods study entailed a desk review of policies and documents and in-depth interviews with 100 caregivers, employees, employers, health worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…While it is important to acknowledge the existence of LMDs regulating or prohibiting specifically BMS marketing in digital and social media, these results highlight that further efforts are needed to improve and strengthen legislation in this area, globally. In this regard, it has been reported that existing sanctions imposed on the offender, especially the BMS industry, are not sufficient to encourage compliance with the legislation 57 58…”
Section: Discussionmentioning
confidence: 99%
“…While it is important to acknowledge the existence of LMDs regulating or prohibiting specifically BMS marketing in digital and social media, these results highlight that further efforts are needed to improve and strengthen legislation in this area, globally. In this regard, it has been reported that existing sanctions imposed on the offender, especially the BMS industry, are not sufficient to encourage compliance with the legislation 57 58…”
Section: Discussionmentioning
confidence: 99%
“…The Philippines was among the first countries to implement the Code nationally. 20 The Philippines enacted the Milk Code in 1986 (Executive Order No. 51), adopting the Code into its national legislation (Philippine Government, 1986).…”
Section: Industry Influencementioning
confidence: 99%